Sistem Informasi Staff dan Pegawai Pada Badan Pusat Statistik Labuhanbatu Berbasis Web - Kamalia, Siti (Universitas Labuhanbatu, 2022)
Staff and employee data information for the Labuhanbatu Central Bureau of Statistics (BPS) office, with information on staff and employee data, we can find out about a complete staff and employee data info on staff and employee data. The programming language used in making the program in question is Web-based. Making the database uses PHP and MYSQL. System design is done by the waterfall method which is a systematic and sequential model of information system development. The data extraction methods used were interviews, observations, and from the Labuhanbatu Central Bureau of Statistics (BPS) office. The results of making the program are aimed at the Completion of Staff and Staff Information Systems at the Web-Based Labuhanbatu Central Bureau of Statistics. Hopefully with this program, it can improve performance in the process of staff and staff data information from the Central Statistics Agency (BPS) of Labuhanbatu.